2017
DOI: 10.1111/nmo.13278
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory events in infants with gastroesophageal reflux symptoms: Is there any association?

Abstract: The simultaneous evaluation of CR and GER events could be useful to identify infants with severe GER and significant temporal associations between these events. Treatment of GER could be indicated in these infants, but as the GER events involved are mainly non-acidic, empirical treatment with antacids is, often, inappropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…9 Nevertheless, in the latest decade, MII/pH data has led to improvements in our knowledge of GER pathophysiology and has helped assess the relationship between GER events and symptoms. [10][11][12][13] MII/pH can detect all types of GER events, and these events can be classified according to concomitant changes in the intra-esophageal pH. 7,14 Furthermore, MII/pH allows us to analyze the relationship between GER events and symptoms through methods such as the symptom index (SI), symptom sensitivity index, and symptom association probability (SAP) index.…”
Section: Introductionmentioning
confidence: 99%
“…9 Nevertheless, in the latest decade, MII/pH data has led to improvements in our knowledge of GER pathophysiology and has helped assess the relationship between GER events and symptoms. [10][11][12][13] MII/pH can detect all types of GER events, and these events can be classified according to concomitant changes in the intra-esophageal pH. 7,14 Furthermore, MII/pH allows us to analyze the relationship between GER events and symptoms through methods such as the symptom index (SI), symptom sensitivity index, and symptom association probability (SAP) index.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and the United States, almost half of all board-certi ed neonatologists believe that apnea is caused by GERD and are likely to recommend acid suppressors (14,15). Cresi et al found the associations of GER and cardiorespiratory events such as apnea existed in 12% of infants and most of them were caused by non-acidic re ux events (6). But some studies speculated that there is no relationship between apnea and GER in preterm infants (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were gestational age (GA) ≤ 32 weeks and clinical symptoms indicative of GER (including apnea, cyanosis, recurrent vomiting, aspiration pneumonia, poor weight gain) according to the criteria of the North American Society for Pediatric Gastroenterology and Nutrition (5). Apnea was de ned as breathing pauses lasting for more than 20 s, or for more than 10 s together with bradycardia or oxygen desaturation (6). Cyanosis was judged by blood oxygen desaturation below 80%.…”
Section: Methodsmentioning
confidence: 99%
“…CR events were defined as episodes of apnoea lasting more than 20 seconds or over 5 seconds if followed by desaturation or bradycardia, episodes of desaturation with blood oxygen saturation below 80%, and episodes of bradycardia with heart rate below 80 beats per minute. (7,19) Minimum duration of bradycardia and blood oxygen desaturation events to be considered for the analysis was 4 seconds.…”
Section: Cr Monitoringmentioning
confidence: 99%
“…The GER events involved in these associations are mainly weakly acidic suggesting that the empirical treatment with antacids is, in most of these cases, inappropriate. (4,7) The proper approach to the problem of GER in preterm infants should be aimed at improving feeding tolerance by adopting techniques and behaviors involving nutrition strategies (thickening of feeds, positioning, slow feeding) and able to reduce the frequency of refluxes. Among these strategies the choice of the most proper nutrition can also influence GER.…”
Section: Introductionmentioning
confidence: 99%